Identifying outdoor assembly sites in early medieval England - Baker, John; Brookes, Stuart (Maney, 2015)
Venues of outdoor assembly are an important type of archaeological site. Using the example of early medieval (Anglo-Saxon; 5th–11th centuries A.D.) meeting places in England we describe a new multidisciplinary method for identifying and characterizing such sites. This method employs place name studies, field survey, and phenomenological approaches such as viewshed, sound-mark, and landscape character recording. While each site may comprise a unique combination of landscape features, it is argued that by applying criteria of accessibility, distinctiveness, functionality, and location, important patterns in the characteristics of outdoor assembly places emerge. Our observations relating to Anglo-Saxon meeting places have relevance to other ephemeral sites. Archaeological fieldwork can benefit greatly by a rigorous application of evidence from place name studies and folklore/oral history to the question of outdoor assembly sites. Also, phenomenological approaches are an important in assessing the choice of assembly places by past peoples